Therapeutic Strategies to Activate p53 - Angelo Aguilar; Shaomeng Wang (MDPI AG, 2022)
The p53 protein has appropriately been named the "guardian of the genome". In almost all human cancers, the powerful tumor suppressor function of p53 is compromised by a variety of mechanisms, including mutations with either loss of function or gain of function and inhibition by its negative regulators MDM2 and/or MDMX. We review herein the progress made on different therapeutic strategies for targeting p53.